Respon Petani Penerima Klaim dan Pemanfaatan Dana Klaim Asuransi Usahatani Padi (Autp) di Subak Puakan, Desa Tengkudak, Kabupaten Tabanan, Bali - AIRLANGGA WIJAYA; IDA AYU LISTIA DEWI; NI LUH MADE INDAH MURDYANI DEWI (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2022)
Farmer Responses and Utilization of Rice Farming Crop Insurance Insurance (AUTP) Funds in Subak Puakan, Tengkudak Village, Tabanan Regency, Bali The Rice Farmer Crop Insurance Program (AUTP) is a program from the Indonesian government with the aim of providing guarantees to rice farmers to reduce the risk. Claim Provide compensation as a form of transfer of risk of financial loss for farmers. This research aims to determine 1) the utilization of rice farming insurance funds by farmers for rice farming compared to non-rice farming, and the comparison of claim funds with production costs, 2) farmers' responses to the rice farming insurance program. The research location was determined by purposive method, in Subak Puakan, Tengkudak Village, Tabanan. Respondents in this study found 59 farmers who received claim funds. Types of data used in the form of primary data and secondary data. The analysis uses quantitative and qualitative data analysis. The results showed that the funds received made all claim recipients claim to continue rice farming. This is in accordance with the aim of the insurance program, which is for farmers to continue rice farming amidst the challenges they face. claims to be able to help farmers as production costs in the next growing season. Claims received have not fully helped cover production costs because the rate of increase was wider after the survey submitted claims which resulted in an increase in the value of losses. The response of farmers to the largest AUTP program is in the negative category (not good and very bad). The negative response was caused by the lack of socialization and the lack of farmer participation in the AUTP program in Subak Pukan. The government together with the insurance program organizers need to review the provisions on the minimum level of damage for filing claims, and the mechanism for further monitoring in the event of wider damage.